Implementation of Integrative Learning Model in Enhancing Indonesian Literature Appreciation Skills among High School Students - Muhammad Nur Iman; Nurasia Natsir (International Journal of Studies in International Education, 2025)
This study investigates the effectiveness of an integrative learning model in improving Indonesian literature appreciation skills among high school students. A quasi-experimental design was employed, involving 120 eleventh-grade students from two public high schools in Jakarta, Indonesia. The participants were divided into two groups: the experimental group, which received instruction through the integrative learning model, and the control group, which followed traditional teaching methods. The integrative model was designed to combine language skills development—such as reading comprehension, vocabulary enrichment, and critical writing—with structured literary analysis focusing on themes, characterization, style, and cultural context. Data were collected using pre-test and post-test assessments to measure learning outcomes, observation sheets to monitor classroom activities, and student questionnaires to capture perceptions and engagement levels. The results indicated that students in the experimental group experienced a significantly higher improvement in literature appreciation skills compared to those in the control group (p < 0.05). They demonstrated enhanced abilities to interpret literary works, analyze narrative elements, and articulate critical responses to Indonesian contemporary literature. Observation data revealed that the integrative approach fostered more active participation, collaborative learning, and deeper reflection during classroom discussions. Moreover, student feedback highlighted increased motivation, enjoyment, and perceived relevance of literature learning to real-life experiences. These findings underscore the pedagogical potential of integrative learning models in secondary school literature education. By linking language proficiency with analytical and interpretative competencies, this approach not only strengthens students’ linguistic abilities but also cultivates their critical thinking, cultural awareness, and aesthetic appreciation. The study recommends the wider adoption of integrative methods in Indonesian high schools as an effective strategy for promoting meaningful and enduring engagement with literature.